"Comparative (bio)economic systems" in terms of social responsibility: The natural environment : between ideal capitalism, utopian socialism and real-world interventionism - Mihaela Iacob; Rodica Gherghina; Georgiana Camelia Crețan (Amfiteatru Economic Journal, 2019)
Comparative judgements related to economic systems (along with pending political ideologies) represent a subject of investigation that, at first glance, appertains to the "ABC" of social sciences, although the "literacy" of policy-makers, business officials, or public opinion reveals surprising understanding flaws. The academic environment - where there is a tacit consensus on the interdisciplinary character of such an approach, on the perpetual relevance within the various (sub)disciplines, and on the somewhat exhaustion of the subordinated debates - remains subtly divided on a series of theoretical delimitations or historical evidence. This article aims to highlight a (sub)domain of the comparative analysis regarding the economic systems in which the literature is not as polarized as it is rarefied: what roots and reverberations does "social responsibility" have within the main economic systems and where and how its "ecological sustainability" component manifests itself? The present research targets to critically and originally review, in a "bioeconomic" key, the way in which social responsibility underlying sustainability is perceived, penetrated and practiced within pure liberal capitalism / market economy, canonical socialism / command economy, and real-world interventionism / mixed economy, offering both a priori insights and empirical illustrations.
Keywords: M14; P50; Q56; 330; social responsibility; bioeconomy; economic systems; capitalism; socialism; interventionism; sustainability